1993
DOI: 10.1007/bf01313770
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 production and cell-activation response to cytomegalovirus infection of vascular endothelial cells

Abstract: Human cytomegalovirus (HCMV) is a source of major complications in immunosuppressed individuals, and endothelial involvement in HCMV infection is well documented. Traditionally laboratory strains of HCMV have been used in experimental investigations in vitro; however the continuous propagation of these strains in fibroblasts have attenuated the virus making it unsuitable for infecting other cell systems such as endothelial cells. In this study a recent clinical isolate of HCMV was propagated through several pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…IL-1 scrum levels were not elevated during HCMV infection after orthotopic liver transplantation [200], In situ hybridization analyses revealed that in HCMV-infected lungs, there was local expression of IL-1 in reactive macrophages and endothelial cells, whereas infected cells themselves did not express IL-1 [212], Con sistent with the latter finding are observations in infected endothelial cell cultures, demonstrating autocrine secre tion of IL-1 at late times after infection while the cytokine remained undetectable in the culture supernatant [62]. At early times after infection, IL-I levels in the supernatant of cultured endothelial cells even seem to be decreased [91], In transient expression systems, transfection of the IE1 gene led to upregulation of the IL-1 promoter in the lipopolysaccharide-stimulated monocytic cell line THP1 [213]. In infected cultured monocytes, an IL-1 upregula tion was accompanied, however, by a clear decrease in biologic IL-1 activity [214], An inhibitory factor, ex pressed together with IL-1.…”
Section: Humoral Pathogenicitymentioning
confidence: 50%
“…IL-1 scrum levels were not elevated during HCMV infection after orthotopic liver transplantation [200], In situ hybridization analyses revealed that in HCMV-infected lungs, there was local expression of IL-1 in reactive macrophages and endothelial cells, whereas infected cells themselves did not express IL-1 [212], Con sistent with the latter finding are observations in infected endothelial cell cultures, demonstrating autocrine secre tion of IL-1 at late times after infection while the cytokine remained undetectable in the culture supernatant [62]. At early times after infection, IL-I levels in the supernatant of cultured endothelial cells even seem to be decreased [91], In transient expression systems, transfection of the IE1 gene led to upregulation of the IL-1 promoter in the lipopolysaccharide-stimulated monocytic cell line THP1 [213]. In infected cultured monocytes, an IL-1 upregula tion was accompanied, however, by a clear decrease in biologic IL-1 activity [214], An inhibitory factor, ex pressed together with IL-1.…”
Section: Humoral Pathogenicitymentioning
confidence: 50%
“…The use of antibodies to inhibit the adhesion of leukocytes to cytokine-activated endothelial cells has been used regularly to characterize molecules involved in leukocyte-endothelial cell adhesion (2,8,26). However, to confirm the results of the adhesion inhibition assay, we used flow cytometric analysis to investigate the changes in the expression of these adhesion molecules on mock-and HCMV-infected HUVEC.…”
Section: Discussionmentioning
confidence: 99%
“…The supernatants were harvested and stored at -80 C until use. The virus-free supernatants were free of infectious virus when the production of CPE (at 14 days post challenge) and the presence of immediate-early/early antigen (at 24 hr post challenge), were investigated (26).…”
mentioning
confidence: 99%
“…In this system we have compared the effect on leukocyte adhesion of infecting aortic endothelial cells with CAEV with that of treatment with TNFa, an initiator of the sequence of events leading to expression of the endothelial cell surface molecules involved in leukocyte transmigration. Viral infection has frequently been shown to activate endothelial cells and thereby affect leukocyte adhesion, and the lentiviruses HIV and SIV are known to infect endothelial cells [1,15,27]. Activation of human endothelial cells by West Nile virus results in increased expression of MHC class II molecules and of adhesion molecules [24].…”
Section: Introductionmentioning
confidence: 99%